2005
DOI: 10.1577/h04-005.1
|View full text |Cite
|
Sign up to set email alerts
|

Fish Disease and Biosecurity: Attitudes, Beliefs, and Perceptions of Managers and Owners of Commercial Finfish Recirculating Facilities in the United States and Canada

Abstract: In recirculation finfish facilities in the United States and Canada, biosecurity utilization is neither consistent nor uniform. Seeking reasons for this situation, we examined the beliefs, perceptions, and attitudes of managers and owners of such facilities about fish disease and biosecurity utilization. A questionnaire was mailed in the fall of 2001 to the managers and owners of 152 finfish-rearing recirculation facilities in the United States and Canada to gather information on their attitudes, beliefs, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
1
13
0
2
Order By: Relevance
“…The quantitative study covered topics related to Themes 1 to 6 of the If a pig farmer is familiar with the clinical signs of CSF, he is in the best position to detect this disease, because he is on the frontline of animal disease identification and responsible for biosecurity measures. Our qualitative findings demonstrated that biosecurity behavior (practices employed on farms to prevent and/or control disease) are influenced by levels of awareness or knowledge about biosecurity, which is in line with previous research (Delabbio et al, 2003(Delabbio et al, , 2004(Delabbio et al, , 2005Lawson et al, 2001;Heffernan et al, 2008). Farmers' knowledge and awareness of the disease and their willingness to report the disease, was called vigilance towards disease by Hopp et al (2007).…”
Section: Questionnairesupporting
confidence: 89%
“…The quantitative study covered topics related to Themes 1 to 6 of the If a pig farmer is familiar with the clinical signs of CSF, he is in the best position to detect this disease, because he is on the frontline of animal disease identification and responsible for biosecurity measures. Our qualitative findings demonstrated that biosecurity behavior (practices employed on farms to prevent and/or control disease) are influenced by levels of awareness or knowledge about biosecurity, which is in line with previous research (Delabbio et al, 2003(Delabbio et al, , 2004(Delabbio et al, , 2005Lawson et al, 2001;Heffernan et al, 2008). Farmers' knowledge and awareness of the disease and their willingness to report the disease, was called vigilance towards disease by Hopp et al (2007).…”
Section: Questionnairesupporting
confidence: 89%
“…Animal handlers’ actions however are an outcome of beliefs, perceptions and attitudes about those activities [20]. Several previous studies have linked the perceptions and attitudes of animal handlers to their infection control/biosecurity behaviour [20-24].…”
Section: Introductionmentioning
confidence: 99%
“…Animal handlers’ actions however are an outcome of beliefs, perceptions and attitudes about those activities [20]. Several previous studies have linked the perceptions and attitudes of animal handlers to their infection control/biosecurity behaviour [20-24]. It is important to consider animal managers’ biosecurity risk perceptions and integrate them into animal health education campaigns in order for the campaign to be effective [20].…”
Section: Introductionmentioning
confidence: 99%
“…En effet, la biosécurité permet de diminuer le risque d'introduction de maladies (Shane 1993) et de réduire les pertes financières suite à une infection (Gifford et al 1987). Cependant, dans plusieurs secteurs, la pratique de la biosécurité ou son observance est sporadique et variable, que ce soit dans les élevages bovins (Rauff et al 1996 ;Thomson 1997 ;Godkin 1999 ;Sanderson et al, 2000 ;Wren 2000 ;Faust et al 2001 ;Hoe & Ruegg, 2006), porcins (Losinger et al 1998 ;Amass & Clark, 1999 ;Broes 2002 ;Pinto & Urcelay, 2003), aviaires (Nespeca et al 1997 ;Vaillancourt & Carver, 1998) ou dans les exploitations aquacoles (Delabbio et al 2004(Delabbio et al , 2005Bondad-Reantaso et al 2005). Haynes et ses collègues (1979) définissent l'observance comme étant le comportement d'une personne qui suit la recommandation médicale, par exemple, prendre des médicaments, suivre un régime ou effectuer un changement de style de vie.…”
Section: L'observance Et Son éValuation ; Rappels Bibliographiquesunclassified
“…Il semble donc que ces facteurs humains jouent un rôle important sur l'observance (Delabbio et al 2003(Delabbio et al , 2005. Par contre, les associations décrites dans ces articles n'ont pas été scientifiquement confirmées, mais plutôt suggérées par les auteurs.…”
Section: L'observance Et Son éValuation ; Rappels Bibliographiquesunclassified